Respostas

2014-08-14T19:10:21-03:00
Oi Paloma.

4cos^{ 2 }x+5senx-5=0\\ \\ sen^{ 2 }x+cos^{ 2 }x=1\\ cos^{ 2 }x=1-sen^{ 2 }x\\ \\ 4(1-sen^{ 2 }x)+5senx-5=0\\ 4-4sen^{ 2 }x+5senx-5=0\\ -4sen^{ 2 }x+5senx-1=0\quad (-1)\\ 4sen^{ 2 }x-5senx+1=0\\ \\ senx=y\\ \\ 4y^{ 2 }-5y+1=0\\ \\ \Delta =b^{ 2 }-4ac\\ \Delta =(-5)^{ 2 }-4*4*1\\ \Delta =25-16\\ \Delta =9\\ \\ \frac { -b\pm \sqrt { 9 }  }{ 2a }

y^{ 1 }=\frac { 5+3 }{ 8 } \Rightarrow \frac { 8 }{ 8 } \Leftrightarrow 1\\ \\ y^{ 2 }=\frac { 5-3 }{ 8 } \Rightarrow \frac { 2 }{ 8 } \Leftrightarrow \frac { 1 }{ 4 } \\ \\ senx=\frac { 1 }{ 4 }